MEMORI KOLEKTIF KAWASAN “LITTLE TOKYO” PADA “TEMPAT KETIGA” BLOK M - Michael Hutagalung; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2023)
Blok M area is a part of Jakarta that is very popular with visitors and known for its endless activities. Because the Blok M area is an office and commercial area to meet daily primary and secondary needs. As a result of intense activity, the area of ​​Blok M has undergone some degradation of the region, such as physical, social, and spiritual degradation, which has changed the image of the place. Blok M area, known as